Socialization and Education on the Utilization of Vitamins in the Bogor Court Public Elementary School Environment - Zunnita, Oktaviana; Herlina , Eka; Jakaria, Muhamad; Kurniasari , Devi (Jurnal Pengabdian Masyarakat Inovatif, 2023)
Vitamins are complex compounds that are needed in small amounts by the body. Vitamins function to help regulate or process body activities. without vitamins the body will experience health problems. Considering the great benefits of vitamins, the Indonesian Ministry of Health issued '10 Balanced Nutrition Guidelines' through the Healthy Living Community Movement (GERMAS). By implementing these guidelines, it is hoped that the community, especially school-age children, will have a stronger immune system, in order to avoid a number of diseases.  Vitamin A is always given in February and August at an early age. Vitamin A/retinol is involved in the formation, production, and growth of red blood cells, and lymphocyte cells During the pandemic, for the prevention and cure of diseases caused by the covid 19 virus, vitamins C, D and E have a role in therapeutic management. Therefore, it is necessary to introduce the benefits of vitamins starting at elementary school age, by providing socialization and education to parents, teachers and school committees. Socialization and education of the benefits of vitamins in the environment of SD Negri Pengadilan Bogor, conducted online, as well as visits to Pakuan Farma Pharmacy. Parents, teachers and school committee were given education about giving vitamins according to the daily dose, types of water and fat soluble vitamins, in the form of materials and leaflets. In addition, the material provided is about how to dispose of unused vitamins and the vitamin content contained in fruits and vegetables. The results of the PKM showed an increase in knowledge about the benefits of vitamins. It can be concluded that adequate consumption of vitamins and diverse foods with balanced nutrition can increase the potential for achievement in oneself which plays an important role in child development, namely smart, creative, outgoing, independent and confident.